Pengaruh Kompensasi Finansial dan Beban Kerja Terhadap Kepuasan Kerja Karyawan - Tri Widiastuti, Desak Nyoman; Wimba, Gusti Ayu; Widani Sugianingrat, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Job satisfaction for every employee is the key to a company where company goals can be achieved if employees get job satisfaction as expected. The purpose of this study was to determin the effect of financial compensation and workload on employee job satisfaction. Sampling using probability method with the number of respondents 84 people. The data analysis method used was multiple linier regression analysis using SPPS 23 For Windows. The results of data analysis show that financial compensation has a positive and significant effect on job satisfaction, workload has a negative and significant effect on job satisfaction, and simultaneously financial compensation and workload can explain the effect on job satisfaction by 62,9% the rest is influenced by other variables. Outside of this research. Based on the results of the study, the company should increase financial compensation and minimize workload will result in job satisfaction of employees of PT. Canning Indonesian Products in Denpasar.